Robust atomic states for quantum information with continuous variables - Vudayagiri, Ashok; Sankhari, Bappaditya (Frontiers in Quantum Science and Technology, 2023)
Using a set of Zeeman sublevels of an alkali atom such as rubidium or sodium, we propose to construct a pair of coherentc population trap (CPT) states, which can be individually addressed and populated at will. The system can be arranged such that there exists a dressed state that is a linear combination of these two CPT states. We have earlier shown the capability of forming discrete quantum gates using this configuration [J.Phys. B, (2006), 39, 3919]. In the present communication, we will show how the same configuration can be used to prepare and operate continuously varying states. The state can be mapped to a 2D parametric space in such a way that any desired vector within it can be prepared, and a continuous, adiabatic evolution from one vector to another is also possible. A method to exploit a continuous interaction potential, which can be used in quantum computation, is also suggested. We discuss how a continuous variable quantum computation can be performed using such states.